STRATEGI PEMASARAN DESA WISATA DIGITAL TAMAN KEHATI MELALUI WEBSITE, DESA DUKUHDALEM, KECAMATAN JAPARA, KABUPATEN KUNINGAN, JAWA BARAT : strategi pemasaran desa wisata digital taman kehati melalui website, desa dukuhdalem kecamatan japara, kabupaten Kuningan - Fitri, Ade Amelia; Komala, Widiani Ica; Sari, Ai Ageng; Nurhayati, Ita; Yuliani, Yuliani; Syahputra, Yayat; Pratama, Muhammad Rizki Putra; Nulhakim, Dede Lukman; Aditiya, Tesa; Sari, Dita Komala (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM Azramedia Indonesia, 2024)
Currently, technological progress is growing rapidly, it can be seen from changes in aspects of human life, technological progress can make work, education, business opportunities easier, and can obtain information from all over the world. A website is a site that can be accessed as a promotional place that can be seen by a wide audience. Dukuhdalem Kehati Park is a park that lacks promotion and many people don't know about it. The aim of this research is that students who serve in Dukuhdalem Village want to introduce Kehati Park through a website so that it can be accessed and seen by a wide range of people, not just the people of Dukuhdalem Village. The method of this activity is to create a website as a digital promotional place that introduces the Biodiversity Park and provides training or how to operate the use of the website to continue to develop. The result of this activity is that the Taman Kehati website can be used to promote the Taman Kehati tourist attraction, this website can also make the Taman Kehati tourist attraction known to the wider community via the internet and can help the village economy.